The effectiveness of 'husband as a birth partner module' in reducing pain and anxiety - Zainab, Mohd Shafie; Rohimah, Ismail; Rohani, Ismail (2016)
Background: The presence of a husband as a birth partner during childbirth is anticipated by the spouse. Most pregnant mothers prefer their husband to be by their side during the childbirth. The objective of the study is to measure the effectiveness of 'Husband as A Birth Partner Module' (HBPM) in reducing pain and anxiety among the wives. Methods: A mix method approach was employed where, phase one is a qualitative study to explore the needs of the HBPM and the second phase is a quasi-experimental to measure the effectiveness of the HBPM. The data were analysed by thematic analysis and SPSS 16.0. Results: Themes identified in the phase one study were 1) support from the husband, 2) roles of the husband, 3) care of pregnancy and birth, 4) comforting measures to reduce childbirth pain and anxiety. The level of anxiety among wives was highly significant (p<0.012) and the F statistic (df) was 6.34 (1,244) in the intervention group. The score of childbirth pain in the intervention group was significantly decreased among the intervention group with a score of 4.85 ± 1.48, whereas the control group had a score of 7.08 ± 1.78 (p<0.001). Conclusions: Promoting childbirth knowledge is an important health programme to enhance the quality of a safe and natural childbirth. Husbands need to be proactive as a birth partner.